Filsafat Pendidikan Ki Hajar Dewantara sebagai Landasan Pendidik di Era Digital - Fitri Sulistyaningrum; Usman Radiana; RR. Eka Ratnawati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This research aims to analyze the relevance and applicability of Ki Hajar Dewantara's educational philosophy in facing the increasingly developing digital era. Ki Hajar Dewantara, as an Indonesian education figure, has rich and deep pedagogical principles. However, in facing significant challenges and changes in the world of education caused by digital technology, the relevance of this traditional approach needs to be evaluated. This article examines Ki Hajar Dewantara's educational principles, such as "ing ngarsa sung tulada, ing madya mangun karsa, tut wuri handayani," and how these principles can be integrated into education in the digital era. The results of this research provide valuable insight into how technology-based education can still respect the values and principles espoused by Ki Hajar Dewantara.